Factors Associated with Clinical Outcomes of Palliative Stenting for Malignant Colonic Obstruction - Sang-Jae Kwon; Jiyoung Yoon; Eun Hye Oh; Jeongseok Kim; Nam Seok Ham; Sung Wook Hwang; Sang Hyoung Park; Byong Duk Ye; Jeong-Sik Byeon; Seung-Jae Myung; Suk-Kyun Yang; Dong-Hoon Yang (Gut and Liver, 2021)
Background/Aims: Self-expandable metal stents (SEMSs) can be applied to relieve colorectal obstruction secondary to incurable primary colorectal cancer or extracolonic malignancy. We aimed to identify factors associated with clinical success and the reintervention-free survival (RFS) after palliative stenting. Methods: Cases of palliative SEMS placement between 2005 and 2019 were retrieved from the institutional database and reviewed retrospectively. Logistic regression and log-rank testing followed by Cox proportional hazard analyses were performed to investigate the predictors of the clinical success of palliative stenting and factors associated with RFS, respectively. Results: A total of 593 patients underwent palliative stenting for malignant colonic obstruction (MCO). The technical and clinical success rates were 92.9% and 83.5%, respectively. Peritoneal carcinomatosis was a predictor of clinical failure (odds ratio, 0.33; 95% confidence interval [CI], 0.17 to 0.65) in the multivariate analysis. Peritoneal carcinomatosis (hazard ratio [HR], 2.48; 95% CI, 1.69 to 3.64) and stent expansion >90% on day 1 (HR, 1.62; 95% CI, 1.05 to 2.50) were associated with a shorter RFS. Neither clinical success nor RFS was associated with extracolonic malignancy. Re-obstruction, stent migration, and perforation were responsible for most reinterventions after clinically successful palliative stenting. Conclusions: In patients requiring palliative stenting for MCO, peritoneal carcinomatosis was associated with both clinical failure and short RFS. Stent expansion >90% on postprocedural day 1 was another predictor of a short RFS after clinically successful stenting. A large prospective study is warranted to establish factors associated with RFS after successful palliative stenting for MCO.